HARTMANN PROCEDURE OR RESECTION WITH PRIMARY ANASTOMOSIS FOR TREATMENT OF PERFORATED DIVERTICULITIS? SYSTEMATIC REVIEW AND META-ANALYSIS - BEZERRA,Rogério Perônico (2020)
ABSTRACT Background: The Hartmann procedure remains the treatment of choice for most surgeons for the urgent surgical treatment of perforated diverticulitis; however, it is associated with high rates of ostomy non-reversion and postoperative morbidity. Aim: To study the results after the Hartmann vs. resection with primary anastomosis, with or without ileostomy, for the treatment of perforated diverticulitis with purulent or fecal peritonitis (Hinchey grade III or IV), and to compare the advantages between the two forms of treatment. Method: Systematic search in the literature of observational and randomized articles comparing resection with primary anastomosis vs. Hartmann’s procedure in the emergency treatment of perforated diverticulitis. Analyze as primary outcomes the mortality after the emergency operation and the general morbidity after it. As secondary outcomes, severe morbidity after emergency surgery, rates of non-reversion of the ostomy, general and severe morbidity after reversion. Results: There were no significant differences between surgical procedures for mortality, general morbidity and severe morbidity. However, the differences were statistically significant, favoring primary anastomosis in comparison with the Hartmann procedure in the outcome rates of stoma non-reversion, general morbidity and severe morbidity after reversion. Conclusion: Primary anastomosis is a good alternative to the Hartmann procedure, with no increase in mortality and morbidity, and with better results in the operation for intestinal transit reconstruction.